EVALUACIÓN FINANCIERA APLICADA A LA EMPRESA DE EXPLOTACIÓN DE CRIADEROS DE CAMARONES DEL SR. MARCO VINICIO CAMPOVERDE PALACIOS, DEL CANTÓN HUAQUILLAS – PROVINCIA DE EL ORO. PERIODOS 2016 - 2017” - Ludeña Severino, Lisenia Katherine (2019)
The research work entitled "FINANCIAL EVALUATION APPLIED TO THE COMPANY OF EXPLOITATION OF SHRIMP BREEDERS OF MR. MARCO VINICIO CAMPOVERDE PALACIOS, DEL CANTÓN HUAQUILLAS - PROVINCE OF EL ORO. PERIODOS 2016 - 2017 "is developed to fulfill the prerequisite to obtain the title of Accounting Engineer and Auditor Accountant Audit. In order to carry out the financial evaluation, it began with the collection of economic-financial data of the company, which consisted mainly of the financial statements, which allowed analyzing the economic and financial structure and making the application of the evaluation methods that they take in counts the value of money over time as the net present value, internal rate of return, cost benefit and equilibrium point, in order to know if the investment made by the owner is profitable, then the financial indicators were applied to know liquidity, activity, indebtedness and profitability, to verify the efficiency with which the shrimp farm operates. The results obtained from the financial evaluation made to the shrimp farm allowed to know that making an investment of $ 624,538.67 generates a profit of $ 241,385.23 considering a period of 10 years for the recovery of capital, it is important to note that the company has a high level of indebtedness surpassing the established standard that is 30%, because the owner manager made a loan with financial institutions.